Sir3-dependent assembly of supramolecular chromatin structures in vitro - Georgel, Philippe T. (The National Academy of Sciences, 2001)
Baculovirus-expressed recombinant Sir3p (rSir3p) has been purified to near homogeneity, and its binding to naked DNA, mononucleosomes, and nucleosomal arrays has been characterized in vitro. At stoichiometric levels rSir3p interacts with intact nucleosomal arrays, mononucleosomes, and naked DNA, as evidenced by formation of supershifted species on native agarose gels. Proteolytic removal of the core histone tail domains inhibits but does not completely abolish rSir3p binding to nucleosomal arrays. The linker DNA in the supershifted complexes remains freely accessible to restriction endonuclease digestion, suggesting that both the tail domains and nucleosomal DNA contribute to rSir3p–chromatin interactions. Together these data indicate that rSir3p cross-links individual nucleosomal arrays into supramolecular assemblies whose physical properties transcend those of typical 10-nm and 30-nm fibers. Based on these data we hypothesize that Sir3p functions, at least in part, by mediating reorganization of the canonical chromatin fiber into functionally specialized higher order chromosomal domains.